2010
DOI: 10.1007/s10439-010-0118-z
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a Semi-Classical Signal Analysis Method for Stroke Volume Variation Assessment: A Comparison with the PiCCO Technique

Abstract: This study proposes a Semi-Classical Signal Analysis (SCSA) method for stroke volume (SV) variations assessment from arterial blood pressure measurements. One of the SCSA parameters, the first systolic invariant (INVS₁), has been shown to be linearly related to SV. To technically validate this approach, the comparison between INVS₁ and SV measured with the currently used PiCCO technique was performed during a 15-min recording in 20 mechanically ventilated patients in intensive care. A strong correlation was es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 31 publications
1
25
0
Order By: Relevance
“…Moreover, κ i,n,h resp. ρ j,m,h are the negative eigenvalues of the one dimensional semi-classical Schrödinger operator given by (17), (resp. (18)…”
Section: Application To Imagesmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, κ i,n,h resp. ρ j,m,h are the negative eigenvalues of the one dimensional semi-classical Schrödinger operator given by (17), (resp. (18)…”
Section: Application To Imagesmentioning
confidence: 99%
“…The element [i, j] is then considered twice, which justifies the 1 2 in the potentials of the one dimensional operators (17) and (18).…”
Section: Algorithm Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is found that, when h tends to zero, the reconstructed spectrum s h converges towards the true spectrum s. This is in compliance with the semi-classical properties of the Schrödinger operator where the number N h of negative eigenvalues and consequently the number of eigenfunctions increases when h decreases. [17][18][19][20][21] Since the main goal of the technique is to separate the useful information from noise, it is preferable to represent the input signal with the minimum number possible of eigenfunctions (SL functions). This is achieved by choosing a large value of the parameter h to minimize N h , and iteratively lowering it to increase N h to include more eigenfunctions until the noiseless spectrum s h is accurately reconstructed.…”
Section: Introductionmentioning
confidence: 99%
“…This is in agreement with the properties of the eigenfunctions ψ(f), where it has been shown that the nth squared eigenfunction ψ 2 nh f ð Þ has n wells, implying that the first squared eigenfunction ψ 2 1h f ð Þ is represented by a single well function localized at its maximum, the second squared eigenfunction ψ 2 2h f ð Þ has two wells, and so on. [17][18][19][20][21] By analogy, one can see that the squared eigenfunctions with low nh values represent, in a broad manner, the profiles of the peaks of the spectrum, whereas the functions with high nh values characterize more the fine details of these profiles. Therefore, by incorporating squared eigenfunctions with higher nh values, the peaks are accurately represented into the reconstructed spectrum s h .…”
Section: Introductionmentioning
confidence: 99%